Pre-modern Islamic Medical Ethics and Graeco-Islamic-Jewish Embryology - Ghaly, Mohammed (Bioethics, 2014)
This article examines the, hitherto comparatively unexplored, reception of Greek embryology by medieval Muslim jurists. The article elaborates on the views attributed to Hippocrates (d. ca. 375 BC), which received attention from both Muslim physicians, such as Avicenna (d. 1037), and their Jewish peers living in the Muslim world including Ibn Jumayʽ (d. ca. 1198) and Moses Maimonides (d. 1204). The religio-ethical implications of these Graeco-Islamic-Jewish embryological views were fathomed out by the two medieval Muslim jurists Shihāb al-Dīn al-Qarāfī (d. 1285) and Ibn al-Qayyim (d. 1350). By putting these medieval religio-ethical discussions into the limelight, the article aims to argue for a two-pronged thesis. Firstly, pre-modern medical ethics did exist in the Islamic tradition and available evidence shows that this field had a multidisciplinary character where the Islamic scriptures and the Graeco-Islamic-Jewish medical legacy were highly intertwined. This information problematizes the postulate claiming that medieval Muslim jurists were hostile to the so-called ‘ancient sciences’. Secondly, these medieval religio-ethical discussions remain playing a significant role in shaping the nascent field of contemporary Islamic bioethics. However, examining the exact character and scope of this role still requires further academic ventures.